Isothiazolinones are still widely used in paints purchased in five European countries: a follow-up study - Thomsen, Andreas V.; Schwensen, Jakob F.; Bossi, Rossana; Banerjee, Piu; Gimenez-Arnau, Elena; Lepoittevin, Jean-Pierre; Liden, Carola; Uter, Wolfgang; White, Ian R.; Johansen, Jeanne D. (Contact Dermatitis, 2018)
BACKGROUND: An increasing incidence of contact allergy to methylisothiazolinone (MI) has been seen, caused, in particular, by cosmetic products and paints. A study from 2015 showed that 93.0% of paints bought in five European countries contained MI. New regulations have been discussed for paints in the EU, which may have influenced this market. OBJECTIVES: To re-evaluate the use and concentrations of MI and four other isothiazolinones in water-based wall paints. METHODS: Water-based white wall paints (n = 60) were purchased in retail stores in five European countries: Denmark, France, Germany, Sweden, and the United Kingdom. The paints were analysed for isothiazolione content by the use of high-performance liquid chromatography coupled to ultraviolet detection, and the results were confirmed with high-performance liquid chromatography-tandem mass spectrometry. RESULTS: MI was identified in 55 (91.7%) of the paints, with concentrations ranging from 1.1 to 142.7 ppm. The other isothiazolinones were identified in 20.0% [methylchloroisothiazolinone (MCI)] to 88.3% [benzisothiazolinone (BIT)] of the paints. BIT concentrations varied significantly between countries, whereas MI and MCI concentrations did not. There were no statistically significant differences in MI, MCI and BIT concentrations between the current study and the 2015 study. CONCLUSIONS: MI and other isothiazolinones are widely used in paints available in Europe. Their use does not seem to be decreasing.
EVALuna2:35682